A review on contribution of landscape settings in hot-humid region towards modification of outdoor microclimate - Mohamad, Amira Nadhirah; Abu Bakar, Aniza; Sanusi, Aliyah Nur Zafirah (2014)
Urban Heat Island (UHI) is an environmental hazard that may greatly deteriorate human health and quality of life due to the high heat dissipation and air temperature that leaves parenthetical stress on human psychology (Shahmohamadi et.al, 2011). On the other hand, UHI worsens the outdoor microclimate and rises the issue of thermal discomfort and deteriorates people's experiences in outdoor spaces. Hence, UHI can be considered as a great challenge in accomplishing a thermal environment in which countries with tropical climate seems to struggle more to achieve their thermal comfort. In the mean time, outdoor environment especially in urban areas which includes its geographical landscape setting and physical built environment properties can be the additional contributing factor in modifying the outdoor microclimate of the area, thus either can enhance or reduce the intensity of UHI. Therefore, this paper reviews literatures on the influence of landscape setting by looking into aspects such as vegetation, ground surface materials and its dimension of built environment as well as their impact towards the outdoor microclimate focusing in Hot-Humid region as a step towards UHI mitigation. Literatures on the climatic and microclimatic occurrences as well as urban climate related studies will also be covered as to provide more understanding on this complex interrelations of various parameters such as air temperature, humidity, wind, solar radiation, built form, vegetations and ground surfaces.